The accounting system of Munch O' Lunch - Hofileña,Eduardo; Javellana, Maricon; Jayoobo, Mayrose; Ledesma, Raissa Ann; Olivares, Marjaneh; Pojol, Mae; Tenefrancia, Rona
An accounting system is an integral component of an enterprise through which information can be gathered as to the effectiveness and efficiency of controls applied on assets, so much so that it has to be carefully studied. However, accounting systems vary in form depending on the nature of the business. Although the subject of this paper is the accounting system, such would only cover the details of the restaurant industry and a particular establishment belonging to the said industry - the Munch O' Lunch. Analysis, recommendations and conclusion will also be provided.